The importance of serotonin in the treatment of functional dyspepsia - Ferrão, Bianca Magalhães; Chehter, Ethel Zimberg (Seven Editora, 2023)
Introduction: Functional dyspepsia (FD) is a gastrointestinal disorder of multifactorial etiology. Although present in about 20% of the world population, there is no satisfactory pharmacological treatment for these patients yet. Considering the fundamental role of serotonin in the pathogenesis of functional gastrointestinal disorders, the objective of this study was to review the literature related to the use of serotonergic drugs in the treatment of FD and assess their effectiveness. Method: We conducted a horizontal review in the PubMed® database on the treatment of FD and serotonin. Articles were selected using the PRISMA method, as well as the keywords “functional dyspepsia treatment” and “serotonin”. Result: We retrieved 180 studies and after eliminating articles based on titles and abstracts, languages other than English and on pathophysiology, 16 studies remained. Discussion: Overall, treatment with prokinetic agents 5-HT4 antagonists cisapride and tegaserod showed improvement in symptoms in patients with FD compared to placebos, while the efficacy of mosapride is still highly questioned. Regarding antidepressants, tricyclics were effective in the treatment of FD, especially amitriptyline in patients with epigastric pain syndrome. Mirtazapine also showed benefits compared to placebo, especially in patients with FD and weight loss. On the other hand, serotonin and norepinephrine reuptake inhibitors and selective serotonin reuptake inhibitors were not effective in the treatment of FD, in addition to causing several adverse effects. The anxiolytics buspirone and tandospirone, responsible for relaxing the gastric fundus, have proven effective for the treatment of FD. Conclusion: Considering the treatment of FD based on serotonergic drugs, tricyclic antidepressants and anxiolytics were the most efficient and indicated in FD cases. The importance of serotonin in the treatment of FD and consequently, in the pathophysiology of the gastrointestinal disorder is demonstrated. DOI:https://doi.org/10.56238/ciesaudesv1-006